2017
DOI: 10.5897/jtehs2017.0399
|View full text |Cite
|
Sign up to set email alerts
|

Hematotoxicity status of lead and three other heavy metals in cow slaughtered for human consumption in Jos, Nigeria

Abstract: Heavy metals are of public health concern worldwide due to their damaging effects on human and animal health, the environment and life in general. This study assessed concentration levels of some toxic heavy metals: Cadmium (Cd), lead (Pb), copper (Cu) and magnesium (Mg) in blood samples of ten (10)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
1
Order By: Relevance
“…The concentration of Cd in this study is lower than the 0.5mg/kg permissible limit of FAO/WHO for tissues of cow. However, our value was high compared to concentration (mg/kg) range of Cd in blood (0.001 -0.019) reported by Lucky & Temitayo (2017), but lower to the mean blood Cd levels of 5.67mg/kg reported by Okareh & Oladipo (2015) in there study conducted in cows from Southern Nigeria. The environment where these cattle are raised is also contaminated with heavy metals, Miranda et al (2009) have reported that cattle and other ruminants are indicators of environmental contamination with heavy metals.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The concentration of Cd in this study is lower than the 0.5mg/kg permissible limit of FAO/WHO for tissues of cow. However, our value was high compared to concentration (mg/kg) range of Cd in blood (0.001 -0.019) reported by Lucky & Temitayo (2017), but lower to the mean blood Cd levels of 5.67mg/kg reported by Okareh & Oladipo (2015) in there study conducted in cows from Southern Nigeria. The environment where these cattle are raised is also contaminated with heavy metals, Miranda et al (2009) have reported that cattle and other ruminants are indicators of environmental contamination with heavy metals.…”
Section: Discussioncontrasting
confidence: 81%
“…Cd was detected in the blood of all the dairy cows sampled in the study area, this is also inline with the findings of Tomza-Marciniak et al (2011) where they showed that the blood of all Friesian cows sampled under similar management system contained some levels of Cd. Cattle can have elevated levels of Pb in their blood without showing any outward signs of clinical disease (Lucky & Temitayo, 2017). Toxic effects of Pb and Cd were reported in cattle and human due to ingestion of contaminated products containing heavy metals (Cai et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Major towns include Jos, Bukuru, Rukuba, Barkin Ladi, Ganawuri, Vom, and Kigom, which fall within Plateau State. The residents of the area are mainly farmers, miners and civil servants (Plateau State Government, 1991 cited by Lucky & Temitayo, 2017).…”
Section: Methodsmentioning
confidence: 99%